Implantación de Contabilidad en la Empresa Cega International Traders en la ciudad de Loja, periodo del 01 de enero al 30 de abril 2014 - Chumbi Orellana, Lorena del Carmen (2016)
This research paper titled "IMPLEMENTATION OF ACCOUNTING IN THE COMPANY CEGA INTERNATIONAL TRADERS IN THE CITY OF LOJA , PERIOD 01 JANUARY TO 30 APRIL 2014" was prepared as established in the Regulation of Academic Board of the National University Loja , in compliance with a pre- qualify the degree and engineering degree in Accounting and Auditing, Certified Public Accountant Auditor requirement. With the implementation of Accounting compliance given to the objectives, which came to strengthen the financial management of the company, making an important contribution to the growth and development of their economic activity, starting with the design of the Plan and Accounting Manual accordingly to the needs thereof; the development of the initial inventory, recording the value of assets and obligations which opening is given the fiscal year, subsequently verifying the source documentation for the Memorandum, the Daybook is recorded in an orderly and systematic; then he continued with the majorization of each of the accounts resulting from the exercise to continue the Trial Balance, Worksheet and presentation of financial statements, in which the veracity of economic activity and the result is reflected operations of the company, through which it was possible to clearly define each of the accounts and balances, revealing the economic benefits obtained within the specified period, finally the application of financial indicators expressing quantitatively and qualitatively the status of the entity. Concluding that the implementation of accounting orderly and systematic information provided from the Initial Inventory to the financial statements, so be advised Owner take into account the research work will serve as a contribution to the development and growth of your company.